Computational Docking and Dynamics Evaluation of Bioactive Compounds from Pandanus tectorius (NTT) Identified by GC-MS and LC-MS/MS as α-Glucosidase Inhibitors - Andri Prasetiyo; Triviana Maruli Simanjuntak; Masditya Kresna Andinata; Resky Putri Purwitaningsih; Annisa Nurfitriany Syarifuddin; Esti Mumpuni; Partomuan Simanjuntak; Rahmatul Qodriah; Zainur Rahman Hakim (Jurnal Kimia Riset, 2026)
Diabetes mellitus is a chronic metabolic disorder with a continuously increasing prevalence and a high risk of causing various serious complications. Inhibition of the α-glucosidase enzyme is one of the therapeutic approaches used to control postprandial hyperglycemia. however, the side effects and limitations of currently available drugs have encouraged the search for safer natural alternatives. Pandanus tectorius (screw pine) is a medicinal plant traditionally used by communities in East Nusa Tenggara (NTT), Indonesia, to reduce blood glucose levels. This study aimed to identify the bioactive compounds present in the roots and leaves of P. tectorius collected from NTT and to evaluate their potential as α-glucosidase inhibitors. Compound identification was performed using GC–MS and LC–MS/MS analyses, followed by molecular docking, ADMET and Lipinski’s rule of five predictions, and 100 ns molecular dynamics simulations. A total of 13 secondary metabolites were identified, comprising seven compounds detected by GC–MS and six compounds identified by LC–MS/MS. Molecular docking results revealed that apiin exhibited the most favorable rerank score (−119.480 kcal/mol), outperforming the reference inhibitor acarbose (−108.186 kcal/mol). Molecular dynamics analysis demonstrated that cirsimarin displayed the most balanced stability profile based on RMSD, RMSF, and binding energy parameters, whereas chrysosplin exhibited the most favorable binding energy but lower conformational stability. Overall, apiin, cirsimarin, and chrysosplin show promising potential for further development as natural α-glucosidase inhibitor candidates for the treatment of diabetes mellitus.